The urgency of information and communication technology in MI/SD learning - Agus Salam; De Isya; Nurhidayanti; Restu Sholiha; Nila Sari (PPPM STKIP PGRI Lamongan, 2022)
The application of ICT in the learning process greatly affects students' interest in learning, because students get new experiences. For example learning by using computers and projectors, students will be more active and will observe learning carefully. Compared to learning without using technology, students will feel bored if they only listen to the teacher delivering material using only the whiteboard media. Learning through the internet (e-learning) does not require physical needs such as classrooms, teachers and students are facilitated because they can carry out the teaching and learning process anywhere and anytime even remotely. This can be useful for students and teachers who don't have much time to come to schools and classrooms. Not only that, learning through the internet (e-learning) can make students learn independently, so that students have free time to hone skills other than learning done at school. The application of technology in the form of an LCD projector can make it easier for students to receive learning materials because students are actively involved in the learning process. Using an LCD projector can also increase students' interest in learning so that the learning process is more interesting and fun for students. Arie Kurniawan said that during the learning process that utilizes ICT students have high learning inspiration compared to people who do not use ICT because students show positive reactions when using ICT in the learning system.